Dietary Lasia spinosa Thw. improves reproductive performance of aged roosters - Hong, Yongxing; Zhang, Lang; Liu, Xingting; Wu, Sile; Wen, Jian; Sun, Haodong; Tian, Kui; Jia, Xiaoxuan; Liao, Yuying; Suthikrai, Wanwipa; Tharasanit, Theerawat; Lu, Yangqing (Frontiers in Nutrition, 2022)
The application of artificial insemination is particularly, owing to which breeder animals are considered an important resource in breeding farms. However, the reproductive performance of roosters typically declines with age, and the economic loss experienced by breeders is attributable to this shortened reproductive lifespan. Lasia spinosa Thw. (LST) reportedly improved reproductive capacity in male rodents. The objective of this study was to investigate the effects of LST on the reproductive performance of aged roosters. Male Guangxi Partridge chicken (mean weight, 3032.41 ± 34.48 g; age, 500 days; n = 72) randomly received the following three dietary treatments: LST0 group (a basal diet), LST2 group (a basal diet with 2% LST powder), and LST4 group (a basal diet with 4% LST powder). Computer-aided sperm analysis revealed that dietary LST supplementation significantly improved semen volume, sperm motility, and concentration. Furthermore, the most potent effects were observed in the treatment group with the administration of 2% LST, which significantly improved the weight of the testes. Hematoxylin-eosin staining revealed the increase in diameter of the seminiferous tubule and height of the seminiferous tubule epithelium possibly caused as a result of LST treatment. A significant increase in fructose and glucose concentrations were observed in the testis and seminal plasma; in addition, a significant increase was observed in the α-glycosidase levels in the testis and spermatozoa. However, the monoaldehyde levels in the spermatozoa appeared to decline significantly. Additionally, the fertility rate increased significantly following 2% LST supplementation. RNA-seq analysis revealed that 34 and 16 unigenes were upregulated and downregulated, respectively, in testicular tissues from roosters that received dietary supplementation of 2% LST. The assigned functions of the unigenes revealed that LST primarily influenced the mechanisms underlying catalytic activity and cellular processes. Kyoto Encyclopedia of Genes and Genomes enrichment analysis suggested that spermatogenesis-related pathways were significantly enriched, including ABC transporters, ribosome biogenesis in eukaryotes, and VEGF, cAMP, and ErbB signaling pathways.